Acetalization of glycerol using mesoporous MoO3/SiO2 solid acid catalyst - Shubhangi B. Umbarkar; Kotbagi, Trupti V.; Biradar, Ankush V.; Pasricha, Renu; Chanale, Jyoti; Dongare, Mohan K.; Mamede, Anne-Sophie; Lancelot, Christine; Payen, Edmond (Journal of Molecular Catalysis A-Chemical, 2009)
Acetalization of glycerol with various aldehydes has been carried out using mesoporous MoO3/SiO2 as a solid acid catalyst. A series of MoO3/SiO2 catalysts with varying MoO3 loadings(1-20 mol%) were prepared by sol-gel technique using ethyl silicate-40 and ammonium heptamolybdate as silica and molybdenum source respectively. The sol-gel derived samples were calcined at 500 degrees C and characterized using various physicochemical characterization techniques. The XRD of the calcined samples showed the formation of amorphous phase up to 10 mol% MoO3 loading and at higher loading of crystalline alpha-MoO3 on amorphous silica support. TEM analyses of the materials showed the uniform distribution of MoO3 nanoparticles on amorphous silica support. Raman spectroscopy showed the formation of silicomolybdic acid at low Mo loading and a mixture of alpha-MoO3 and polymolybdate species at high Mo loadings. Moreover the Raman spectra of intermediate loading samples also suggest the presence of beta-MoO3. Acetalization of glycerol with benzaldehyde was carried out using series of MoO3/SiO2 catalysts with varying MoO3 loadings (1-20 mol%). Among the series, MoO3/SiO2 With 20 mol% MoO3 loadings was found to be the most active catalyst in acetalization under mild conditions. Maximum conversion of benzaldehyde (72%) was obtained in 8 h at 100 degrees C with 60% selectivity for the six-membered acetal using 20% MoO3/SiO2. Interestingly with substituted benzaldehydes under same reaction conditions the conversion of aldehydes decreased with increase in selectivity for six-membered acetals. These results indicate the potential of this catalyst for the acetalization of glycerol for an environmentally benign process. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acetalization; Aldehyde; Glycerol; Silicomolybdic acid; solid acid

Activation by pretreatment of Ag-Au/Al2O3 bimetallic catalyst to improve low temperature HC-SCR of NOx for lean burn engine exhaust - More, Pavan M.; Nguyen, Duy L.; Granger, Pascal; Dujardin, Christophe; Dongare, Mohan K.; Shubhangi B. Umbarkar (Applied Catalysis B-Environmental, 2015)
Bimetallic Ag-Au/Al2O3 catalyst was synthesised by successive impregnation of 1% Au and 1% Ag on in-house prepared high surface area alumina (450 m(2)/g). The corresponding monometallic catalysts were also prepared by loading 1% Ag or 1% Au on the same high surface area alumina for comparison. The catalysts were characterised by various physico-chemical techniques and tested for SCR activity under lean burn engine exhaust conditions. Ag-Au/Al2O3 catalyst prepared by successive impregnation method showed considerably higher NO reduction (100%) to N-2 compared to 1% Au/Al2O3 (70%) whereas the activity was comparable with that of 1% Ag/Al2O3 (96%). The effect of various pretreatments on SCR activity of Ag-Au/Al2O3 was studied and pretreatment at 250 degrees C in flow of hydrogen was found to give the best results with 100% NO conversion to N-2 at 353 degrees C. Further ageing of the catalyst under reaction feed at 500 degrees C resulted in considerable increase in low temperature activity of bimetallic catalyst with similar to 40% NO conversion at 222 degrees C. Even though the SCR activity of pretreated Ag-Au/Al2O3 and Ag/Al2O3 were comparable, after ageing the Ag-Au/Al2O3 showed significantly higher NO conversion (95%) compared to Ag/Al2O3 (83%) and Au/Al2O3 (70%). The formation of H-2 and CO due to steam reforming of higher hydrocarbon (decane) was evidenced at the temperature of highest deNO(x) activity. Detailed investigation of the textural properties of the pretreated and aged catalysts showed presence of well dispersed metallic Au and Ag-n(delta+) clusters after pretreatment in hydrogen at 250 degrees C. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Ag-Au bimetallic catalyst; Catalyst ageing; dispersion; Low temperature HC-SCR; Steam reforming